Establishment of a Medical Team in Girimekar Village, Bandung District - Fenti Fatmawati; Patonah Patonah; Dedep Nugraha; Wempi Budiana; Yanyan Mulyani; Supriyatni Kartadarma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Bhakti Kencana University (BKU) community service activities were conducted in Girimekar Village, Bandung Regency. This activity involved BKU lecturers from various disciplines, such as Midwifery, Nursing, Public Health, and Pharmacy. This activity was carried out by forming a medical team, which was an effort to empower the community, especially the youth of the local group. This activity aims to socialize emergency treatment measures that must be carried out as soon as possible before residents are taken to the community health center or hospital. This will help the community care more about their health. Girimekar Village has topography and land contours in the form of highlands and lowlands at an altitude of between 400 meters above sea level and 600 meters above sea level, with an average temperature ranging from 19°C to 37°C. Girimekar Village consists of 5 hamlets, 22 RWs, and 79 RTs. Based on the topography, most areas outside the forest area are slopes or peaks with varying heights. Most RWs are located outside forest areas. Conditions like this are the background for the formation of this medical team. The method for forming a medical team was carried out by identifying the number of young people in the area and then carrying out preliminary outreach by educating them about the importance of emergency treatment before residents are taken to the hospital. After the socialization, the medical team was given training on first aid in the form of basic life support. The formation of the medical team was carried out by first identifying the number of youth. This activity, which was carried out for one month, produced a medical team from among the youth who were expected to be at the forefront in assisting. First, to residents before taking them to the health center or hospital. 26 Girimekar residents attended it, and the long-term plan for this activity is to hold first aid training for the medical team at least once every six months.